Letter from Georg Bredig to Hugh S. Taylor, March 31, 1940 - Bredig, Georg (1940)
Georg Bredig (1868-1944) thanks Hugh S. Taylor (1890-1974) for the kindness and understanding imparted by Taylor and the Princeton University Chemistry Department as Bredig, now in New York City, recovers from his years spent in Germany during the war.
Keywords: Bredig, Georg, 1868-1944; Taylor, Hugh S. (Hugh Stott), 1890-1974; World War (1939-1945); Emigration and immigration; Princeton University